Melastomataceae do Parque Estadual da Serra Dourada, Goiás - Machado, Ana Isa Marquez Rocha (2013)
Serra Dourada State Park is located in the municipalities of Buriti de Goiás, Cidade de Goiás and Mossâmedes, Goiás state. Among the physiognomies of Cerrado the Serra Dourada State Park presents gallery forest, dry forest, campo sujo , campo rupestre , cerrado sentido restrito and cerrado rupestre . The study presents an identification key for the species, descriptions, commentaries about the morphological characters, data about geographic distribution and the flowering and fructification periods of species, analyzes of the different habitat and habits, conservation state of the species, illustrations of some species and the list of collectors of the examined material. Melastomataceae is represented in the area by 43 taxa and 13 genera. Miconia is the most representative genera, with 18 species, followed by Tibouchina, which is represented by 10 taxa, Microlicia has 4 species and Clidemia has 2 species. Acisanthera, Cambessedesia, Desmoscelis, Macairea, Pterolepis, Rhynchanthera, Siphanthera, Tococa and Trembleya are represented by one species each. Microlicia ordinata, Tibouchina crassiramis, T. johnwurdackiana, T. robusta and Trembleya neopyrenaica stand out because of their endemism in Goiás. Serra Dourada State Park is important for the conservation of the flora of Melastomataceae for presenting the second largest number of species for this family in the parks of Goiás State, endemic species and new occurrences for the state.